Agile person identification through personality test and kNN classification technique - Bhannarai R. (2017)
© 2016 IEEE. Agile methodology is a famous software development methodology. The methodology stresses on adaptation and collaboration between people. Here, software project managers should agree to an idea of putting the right people in the right jobs. This research puts forward an idea of applying Big Five Personality Traits to predict how people suitable for the Agile methodology. A predicting method is driven by using kNearest Neighbour (kNN) classification technique. Results of a pilot study are presented and shown that the selected classification technique can be used for the prediction.